Challenges to the Pair Bond: Neural and Hormonal Effects of Separation and Reunion in a Monogamous Primate - Hinde, Katie; Muth, Chelsea; Maninger, Nicole; Ragen, Benjamin J.; Larke, Rebecca H.; Jarcho, Michael R.; Mendoza, Sally P.; Mason, William A.; Ferrer, Emilio; Cherry, Simon R.; Fisher-Phelps, Marina L.; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2016)
Social monogamy at its most basic is a group structure in which two adults form a unit and share a territory. However, many socially monogamous pairs display attachment relationships known as pair bonds, in which there is a mutual preference for the partner and distress upon separation. The neural and hormonal basis of this response to separation from the adult pair mate is under-studied. In this project, we examined this response in male titi monkeys (Callicebus cupreus), a socially monogamous New World primate. Males underwent a baseline scan, a short separation (48 h), a long separation (approximately 2 weeks), a reunion with the female pair mate and an encounter with a female stranger (with nine males completing all five conditions). Regional cerebral glucose metabolism was measured via positron emission tomography (PET) imaging using [18F]-fluorodeoxyglucose (FDG) co-registered with structural magnetic resonance imaging (MRI), and region of interest (ROI) analysis was carried out. In addition, plasma was collected and assayed for cortisol, oxytocin (OT), vasopressin (AVP), glucose and insulin concentrations. Cerebrospinal fluid (CSF) was collected and assayed for OT and AVP. We used generalized estimating equations (GEE) to examine significant changes from baseline. Short separations were characterized by decreases in FDG uptake, in comparison to baseline, in the lateral septum (LS), ventral pallidum (VP), paraventricular nucleus of the hypothalamus (PVN), periaqueductal gray (PAG), and cerebellum, as well as increases in CSF OT, and plasma cortisol and insulin. Long separations differed from baseline in reduced FDG uptake in the central amygdala (CeA), reduced whole brain FDG uptake, increased CSF OT and increased plasma insulin. The response on encounter with a stranger female depended on whether or not the male had previously reproduced with his pair mate, suggesting that transitions to fatherhood contribute to the neurobiology underlying response to a novel female. Reunion with the partner appeared to stimulate coordinated release of central and peripheral OT. The observed changes suggest the involvement of OT and AVP systems, as well as limbic and striatal areas, during separation and reunion from the pair mate.